2017
DOI: 10.1177/2292550317693814
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management in Pierre Robin Sequence: The Vancouver Classification

Abstract: Background: Pierre Robin sequence (PRS) is a triad of micrognathia, glossoptosis, and respiratory distress. There is no standard clinical classification used in the management of neonatal airway in patients with PRS. The goal of our study was to review the presentation and management of patients with PRS and formulate a clinical grading system and treatment algorithm. Methods: A 10-year retrospective review of all neonates diagnosed with PRS was performed after obtaining institutional ethics approval. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…1 However, significantly higher rates of surgical intervention (including distraction osteogenesis and tongue-lip adhesion) and tracheostomy of 19-77% have been reported in several studies which are largely from North American centers. 5,[24][25][26][27] This wide variation in practice with an apparent geographical pattern suggests that physician or treatment center preferences, rather than clinical necessity, may direct RS management.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, significantly higher rates of surgical intervention (including distraction osteogenesis and tongue-lip adhesion) and tracheostomy of 19-77% have been reported in several studies which are largely from North American centers. 5,[24][25][26][27] This wide variation in practice with an apparent geographical pattern suggests that physician or treatment center preferences, rather than clinical necessity, may direct RS management.…”
Section: Discussionmentioning
confidence: 99%
“…As more than 50 syndromes have been associated with PRS and each of these syndromes have a vast heterogenicity in their respective presentations, it often becomes very difficult for clinicians to accurately identify the associated syndrome (3,5). We faced a similar predicament.…”
Section: Discussionmentioning
confidence: 99%
“…PRS occurs in isolation or as a part of other syndromes such as Stickler, velocardiofacial, and Treacher-Collins syndromes (3). Because the severity of symptoms, presence of long-term sequalae, requirement of surgery, and mortality rate in syndromic PRS are much higher than non-syndromic/isolated PRS, early differentiation between the two is beneficial to clinicians as it increases their preparedness and helps them take decisions regarding the management plan (1,4,5). However, the phenotypic heterogenicity of the various associated syndromes, make it very hard for clinicians to distinguish between the two (3).…”
Section: Introductionmentioning
confidence: 99%
“…Syndromic PRS is observed in 27% to 70% of all infants with PRS and shows poorer outcomes than those observed in infants with isolated PRS. A study reported by Li et al 7) determined that syndromic PRS was diagnosed in 47%…”
Section: Case Reportsmentioning
confidence: 99%
“…Although there are no studies comparing each non-surgical intervention, the successful use of NPA insertion has been more frequently reported than other interventions when prone position failed 1,7) . NPA insertion can be tried more easily and immediately without any apparatus-or mask-related discomfort.…”
Section: Case Reportsmentioning
confidence: 99%